2004
DOI: 10.1002/cyto.a.20064
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and simple discrimination of mouse pulmonary dendritic cell and macrophage populations by flow cytometry: Methodology and new insights

Abstract: BackgroundThe need to accurately discriminate dendritic cells (DCs) and macrophages (Mphs) in mouse lungs is critical given important biological differences. However, a validated flow cytometry–based method is still lacking, resulting in much confusion between both cell types.MethodsSingle‐cell suspensions freshly obtained from collagenase‐digested lung tissue were stained with a CD11c‐specific monoclonal antibody, detected using a PE‐Cy5 or APC‐conjugated secondary reagent. Cellular immunophenotype was simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
219
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(237 citation statements)
references
References 31 publications
13
219
1
2
Order By: Relevance
“…Staining for MHC-II revealed that CD11c ϩ CX 3 CR1/GFP ϩ cells also express high levels of MHC-II, whereas CD11c ϩ CX 3 CR1/GFP Ϫ cells are MHC-II low (Fig. 1E), supporting their definition as DC and M⌽, respectively (31). Interestingly, we recently reported the same CX 3 CR1 expression pattern for small intestinal lamina propria DC and M⌽ (33).…”
Section: Cr1 Expression Discriminates Between Pulmonary M⌽ and DCsupporting
confidence: 59%
See 2 more Smart Citations
“…Staining for MHC-II revealed that CD11c ϩ CX 3 CR1/GFP ϩ cells also express high levels of MHC-II, whereas CD11c ϩ CX 3 CR1/GFP Ϫ cells are MHC-II low (Fig. 1E), supporting their definition as DC and M⌽, respectively (31). Interestingly, we recently reported the same CX 3 CR1 expression pattern for small intestinal lamina propria DC and M⌽ (33).…”
Section: Cr1 Expression Discriminates Between Pulmonary M⌽ and DCsupporting
confidence: 59%
“…1A). In addition, lung and alveolar M⌽, but not DC, are autofluorescent (31,32). In this study, we show that lung M⌽ and DC also differ in their expression of the chemokine receptor CX 3 CR1.…”
Section: Cr1 Expression Discriminates Between Pulmonary M⌽ and DCmentioning
confidence: 51%
See 1 more Smart Citation
“…Although F4/80 has been used traditionally as a macrophage-specific surface marker, its use in the lung is compromised by low levels of F4/80 on lung macrophages and expression levels that vary in the context of inflammation (Fig. 2) [48,49]. To increase the purity of lung macrophage preparations for procedures such as adoptive transfers, it may be necessary to add a step to specifically deplete the lung DCs [50].…”
Section: Discussionmentioning
confidence: 99%
“…These two populations share similar cell surface makers and are broadly defined by their expression of complement receptors: CR3(CD11b/CD18) and CR4(CD11c/CD18). 31 Thus we first examined the tissue localization and accumulation of CD11bϩ and CD11cϩ cells in mycobacterium-infected lung by immunohistochemistry. By day 21, there was a large accumulation of both CD11bϩ and CD11cϩ cells in the lung, with the CD11bϩ cells being more abundant in the granuloma ( Figure 1A).…”
Section: Similar Immune Cellular Composition Observed In Airway Lumenmentioning
confidence: 99%